Intramedullary Chondrosarcoma of Proximal Humerus - Pratiksha Yadav; Dolly Thakkar; S. S. Thind (Case Reports in Radiology)
Primary chondrosarcoma is the third most frequent primary malignancy of bone after myeloma and osteosarcoma. It is ranging from slow growing nonmetastasising lesions to highly aggressive lesions. We report a case of primary intramedullary chondrosarcoma of proximal humerus. A 60-year-old female presented with pain and hard swelling involving the left arm for 5 months. Radiograph showed a lucent expansile intramedullary lesion with matrix calcification and associated soft tissue mass. CT confirmed the finding. MRI showed a lobulated lesion which is hyperintense on T2WI with low signal fibrous septae. Increased tracer uptake was seen on bone scan. Histopathology confirmed the radiology diagnosis. The patient underwent wide resection and endoprosthetic reconstruction of proximal humerus.